Monocytes in Icelandic horses: comparison between automatic gating by the ADVIA 2120i, a manual gating method and microscopic differentiation. (November 2015) - Leidinger, E.; Prechtl, G.; Figl, J.; Leidinger, J.
Abstract Inspection of the ADVIA 2120i PEROX cytograms from healthy Icelandic horses revealed a mismatch of the automatic gating (A) for monocytes, resulting in a lower percentage. The raw data of 40 Icelandic horses were transformed to FCS files. Data were imported to WinMDI 2.9 (Purdue Cytometry Laboratories) and gated manually (M). In addition, a manual 200-cell differential (D) was performed. ANOVA was used to test for significant differences. RefVal 2.1 (Toulouse Veterinary School) was used to calculate the reference values by different methods. Significance level was set atP  < 0.05. Monocytes were significantly higher by M compared to A and D, neutrophils were significantly lower for A compared to M, but not for A compared to D. Data were used to calculate the RI as follows: neutrophils (A) 37.7–65.6 % (1.7–4.6 × 109 /L); neutrophils (M): 33.8–61.8 % (1.6–4.3 × 109 /L); lymphocytes (A): 26.0–52.7 % (1.1–4.6 × 109 /L), lymphocytes (M): 28.1–55.5 % (1.2–4.0 × 109 /L); monocytes (A): 1.5–4.6 % (0.1–0.4 × 109 /L); monocytes (M): 3.4–6.9 % (0.2–0.5 × 109 /L). The ADVIA 2120i built-in export function and the use of WinMDI allow a very precise recalculation of cell populations. Icelandic horses reportedly have the lowest monocyte number of all horse breeds. This may be possibly caused by higher MPO activity and/or an inaccuracy of the algorithm used.